An underexploited invisible gold resource in the Archean sulphides of the Witwatersrand tailings dumps - Steve Jason Chingwaru; Bjorn Von der Heyden; Margreth Tadie (Scientific Reports, 2023)
Abstract The tailings dumps originating from gold mining in South Africa’s Witwatersrand still contain notable gold endowments. Most tailings reprocessing operations target a native gold fraction using re-milling and carbon-in-leach extraction; however, up to 50–70% of the remaining gold is still not recoverable and instead discarded to the re-dump stream along with abundant sulphides. The mineralogical deportment of this unrecoverable gold underwent a detailed investigation. Using in situ laser ablation ICP-MS mineral chemistry measurements, we show that this gold that is inaccessible to conventional recovery is hosted preferentially in pyrite and arsenian pyrite. Importantly, complementary optical and electron microscopy observations reveal that the rounded detrital forms of these minerals contain the highest gold concentrations (0.01–2730 ppm), showing some similarity to values reported for sulphides from primary orogenic gold deposits found in surrounding Archean-aged granite-greenstone belt remnants. We suggest that detrital auriferous sulphides have been overlooked by historical primary and secondary beneficiation, and thus represent a large (up to 420 tons Au) and under-exploited Au resource currently residing in easily-mined (surficial) Witwatersrand tailings dumps. We further suggest that targeted re-mining of sulphide mineral fraction has the potential to improve gold recovery, recuperate ‘sweetener’ by-product metals (e.g. Cu, Co, Ni) and directly eliminate heavy metal pollution and acid mine drainage issues associated with surficial tailings dumps.